A novel prognostic nomogram based on imaging and molecular parameters for newly diagnosed extranodal natural killer/T-cell lymphoma patients - Dezhi Huang; Fu Li; Shijia Lin; Jing Xia; Bangdong Liu; Xinlei Li; Naya Ma; Yishuo Duan; Yunjing Zeng; Sha Zhou; Shuhan Tang; Wenqiu Huang; et al. (Haematologica, 2024)
Not available.